Peran Orang Tua Dalam Membentuk Karakter Anak Berdasarkan Surah Luqman Ayat 17-19; Perspektif Tafsir Al-Misbah - Muhammad Fariq, Wan; Rosyada , Amrina; Rahma Dhini, Ulfa (Universitas Majalengka, 2023)
Children are the trust entrusted by Allah SWT to parents to raise them to be sholeh and sholeha children. This shows that parents have a great responsibility for the education of their children. Because the success of parents in raising their children will affect his future. Thus, through QS Luqman verses 17-19 provide examples of how parents educate a child. This study aims to find out what education parents need to instill in a child to have charisma based on QS Luqman verses 17-19. The method used by research is the library research method that refers to various data sources. The results of this study explain that in QS Luqman verses 17-19 there are two forms of education that parents need to instill in their children. The education consists of creed education and moral education. Religious education includes worshiping Allah SWT, carrying out amar ma'ruf and staying away from nahi mungkar, and being patient. While moral education includes not being arrogant / arrogant, always being simple and gentle in word and deed.